A Brief Epidemiologic Review of Psoriasis - Nagham Shaheed Mahmood; Rabab Omran; Anwar A. Abdulla (Medical Journal of Babylon)
Psoriasis is an intricate, long-lasting, immune-mediated inflammatory skin condition that has a genetic origin. The body is affected to varying degrees; it can affect almost the entire body or just a few isolated red, scaly plaques. Psoriatic lesions may remain unchanged for years, growing, decreasing, and regressing over time. As the patient ages, the condition could develop worse or “wax and wane” in intensity. Indeed, examples of primary skin lesions are pustules, macules, papules, and plaques. Psoriasis, however, tends to affect more than just the skin and nails; it can cause inflammatory arthritis and inflammatory bowel disease. Additionally, patients’ symptoms may vary greatly from one another. Skin appearances can manifest at any age and can be either monomorphic or polymorphic. Furthermore, numerous emotionally charged, stressful physiological and psychological events, systemic infections, and environmental factors are associated with the beginning and worsening of the condition. The underlying patho-mechanisms involve complex interactions between the innate and adaptive immune systems. T cells interact with dendritic cells, macrophages, and keratinocytes, which their secreted cytokines can mediate. Biologics targeting tumor necrosis factor, interleukin IL-23, and IL-17 have been developed and approved for treating psoriasis in the past decade. These biologics have dramatically changed the treatment and management of psoriasis.